ANALISIS RISIKO HAZARD DI PT. SUN ENERGY PADA SITE PROJECT PT. PP (PERSERO) MENGGUNAKAN METODE HAZARD AND OPERABILITY STUDY (HAZOP) - Agnes Vicky; Adiasa, Iksan; Ilham Kurnia Sakti Lubis (Hexagon Jurnal Teknik dan Sains, 2024)
As a company that operates in the field of solar power system project development, of course there are many risks at PT Surya Utama Nuansa (SUN Energy), such as during installation and during maintenance. Therefore, employees are required to use personal protective equipment, but based on observations, potential dangers were found in the form of piles of damaged inverters or other materials in random locations and workers lifting solar panels alone, as well as scattered electrical cables. The aim of this research is to provide a solution to reduce the risk of work accidents. The method used in this research is the HAZOP (Hazard and Operability Study) method. Based on the results of the identification and assessment of potential hazards that have been carried out, there are 5 potential hazards, namely a moderate risk level of 27%, a high risk level of 20%, and an extreme risk level of 53%. And it is known that there is a 40% potential hazard in the work attitude classification. 20% on work procedure classification, and 40% on workplace classification. This shows that potential hazards in workplace classification require more attention in efforts to prevent work accidents. It is hoped that this research will implement health and safety at the PT project site. PP (Persero) has been repaired so that it can minimize the occurrence of work accidents while carrying out activities on the site.